(untitled) (Journal of the College of Basic Education, 2022)
The current research aims to :- Know (Evaluation educational website according to international standards in the faculties of education from the point of view of teaching the subject) and the researcher followed the descriptive approach, and the researcher chose a sample of his research intentionally from Tracy, the subject of computers for the first stage in the faculties of education from a group of Iraqi universities, and those included in the research were (25) (Teachers were chosen randomly, and the researcher prepared the research tool, following the following steps: - The researcher developed the proposed vision for the educational website in light of the theoretical background Preparing the search tool (the questionnaire) for the purpose of evaluating the educational website in light of the international standards SCORM. - Applying the research to a sample of (25) computer teachers in the faculties of education, and after looking at the educational website, they were asked to answer the questionnaire prepared for this purpose. After monitoring and analyzing the scores, it was found that: 1- The results obtained from the computer teaching sample and through their answers to the questionnaire, it was found that the percentage was (91%) excellent, and this is a positive indication that the educational website has been accepted by the computer teacher and that it is designed according to the international standards SCORM .